Exploring the ventricular morphology of the heart of Brycon amazonicus (Agassiz, 1829) (Teleostei, Characiformes) - D. dos Santos, Diego [UNESP]; B. Gardinal, Mario V. [UNESP]; R. Ruiz, Thalles F. [UNESP]; Florêncio-Silva, Rinaldo; R. Vidal, Mateus [UNESP]; R. Falleiros-Júnior, Luiz [UNESP]; R. Taboga, Sebartião [UNESP]; B. Franceschini-Vicentini, Irene [UNESP]; A. Vicentini, Carlos [UNESP] (Elsevier, 2025)
Brycon amazonicus, a fish species widely distributed along freshwater rivers in Latin America, is important in maintaining ecological balance. Although some morphological/physiological aspects of B. amazonicus have been reported, the cardiac histomorphology of this species remains poorly understood. Therefore, this study aimed to describe the heart, emphasizing coronary distribution and ventricular myoarchitecture, correlating its structure with its functional activity. Ten adult specimens were anesthetized and perfused with Trident® ink to highlight the coronary branching. Subsequently, the animals were euthanized to collect the hearts, which were collected and processed for histological and histochemical techniques and scanning electron microscopy. We observed that the heart of B. amazonicus has a pyramidal ventricle, mixed myocardium, and coronary vessels restricted to the compact layer, according to classifications in the literature. The compact layer comprises two types of muscle bundles, arranged in longitudinal and circular orientations. The coronary circulation, which originates in the lateral cephalic region, starts from the heart and extends to the ventricular myocardium. Therefore, B. amazonicus has a cardiac morphology similar to that of other teleost species already described in the literature, expanding information on the Characiformes group. The description obtained of the heart of this species may contribute to further studies that seek a better understanding of the ecophysiology and evolution of teleost fish in the freshwaters of the Neotropical region.
Keywords: Anatomy; Morphology; Myocardium; Teleost; Ventricle